Upaya Pelestarian Subak di Perkotaan (Kasus Subak Padanggalak Desa Kesiman Kertalangu Kecamatan Denpasar Timur Kota Denpasar) - PUTU BUDIASTUTI; NI WAYAN ASTITI; WAYAN SUDARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
Abstract The Effort of Subak Preservation in Urban Area (Case Study in Subak Padanggalak, Kesiman Kertalangu Village, Denpasar Timur) The aims of the study are: (1) to examine Subak Padanggalak’s efforts in preserving and sustaining itself for the future on, and (2) to describe the role of goverment and private sector to support the effort in preserving and sustaining Subak Padanggalak. The research location was chosen using purposive method in Subak Padanggalak, Kesiman Kertalangu Village, East Denpasar Sub District, Denpasar. The analysis of this research used a descriptive qualitative method to answer the research questions. Data were collected by using in-depth interviews from eight key informants. The research results show that the efforts made to preserve and to sustain Subak Padanggalak based on the Tri Hita Karana philosophy as follow: (a) parhyangan aspects, subak protects, preserves, and mantains the ritual facilities and conducts routinely the subak’s ritual activities not only in subak level but also in individual level, (b) pawongan aspects, subak makes an agreement to prevent subak land conversion to be non agricultural purposes and also manages irrigation water distribution, and (c) palemahan aspects, subak regularly arranges the mutual cooperation activities related to natural and environmental conservation, irrigation networks and other physical buildings maintenance, efficient land use management, and provides safety situations in subak. Furthermore, the assistance provided by the government and private sector in the form of financial assistance, counseling, coaching, agricultural extension, and jogging track. Keywords: Conservation, Subak, City